المسؤولية الجنائية الدولية للأفراد في الجرائم ضد الإنسانية : دراسة تحليلية - لطيف، سعدون صالح (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
Researcher discussed international criminal responsibility on individual when committing crimes against humanity, and explained the position of individual in international conventional law, when he escapes from international responsibility and the states assume the international legal principles. However, contemporary law highlighted the individual crime responsibility and civil responsibility for the states. The research aims to highlight the individual responsibility when committing international crimes. The researcher has explained the historical development on individual crime responsibility under contemporary international criminal law, and the views of jurist of international law in addressing international criminal responsibility for the individual. He addressed the types of international crimes which is actionable to individual criminal responsibility, and the individual criminal responsibility when committing international crimes and the preventions of that responsibility. He do mention the cults that formed by UN Security Council to judge individuals without considering immunities of their states, and the actions and penal proceedings of those courts. He studied also the crimes committed by the United State of America and its Allies against Iraq people. The researcher used several approaches in this study, including the inductive method, the analytical method and the historical method. The study examined the decisions and regulations on the international criminal law and the opinions of jurists, analyzing, discussing and addressing them in interpreting these opinions in the texts of international legislation and their applicability on the ground, and indicating the stages of the establishment of the judicial courts in the denial of international crimes and the appearance of the Temporary International Courts to the International Criminal Court. The researcher came to a number of conclusions, including: The individual has an international legal personality, for the recognition of international law contemporary international personality and bear all international obligations, the individual who commits an international crime, which falls within the jurisdiction The International Tribunal shall be held responsible as an individual and shall be punished, regardless of its official character, and shall not be regarded as an original actor or accessory to the crime. The researcher also made many recommendations and suggestions for the benefit of the study.